Aerosol light absorption alleviates particulate pollution during wintertime haze events - Jiarui Wu; Naifang Bei; Yuan Wang; Xiaoli Su; Ningning Zhang; Lili Wang; Bo Hu; Qiyuan Wang; Qian Jiang; Chenchong Zhang; Yangfan Liu; Ruonan Wang; et al. (Proceedings of the National Academy of Sciences, 2025)
Aerosol light absorption has been widely considered as a contributing factor to the worsening of particulate pollution in large urban areas, primarily through its role in stabilizing the planetary boundary layer (PBL). Here, we report that absorption-dominated aerosol–radiation interaction can decrease near-surface fine particulate matter concentrations ([PM 2.5 ]) at a large-scale during wintertime haze events. A “warm bubble” effect by the significant heating rate of absorbing aerosols above the PBL top generates a secondary circulation, enhancing the upward motion (downward motion) and the convergence (divergence) in polluted (relatively clean) areas, with a net effect of lowering near-surface [PM 2.5 ]. Furthermore, aerosol absorption of ultraviolet-wave light effectively reduces the photolysis of chemical species, i.e., aerosol–photolysis interaction, hindering ozone formation, reducing atmospheric oxidizing capability, and suppressing secondary aerosol concentrations. Our model assessment reveals that the synergetic two effects decrease near-surface [PM 2.5 ] by around 7.4%, so the presence of light-absorbing aerosols can considerably alleviate particulate pollution during wintertime haze events. Such negative feedbacks to the aerosol loading should be considered in weather/climate prediction and health assessment models.